Heifer replacement: a decision tool to determine if it is more economical to buy or raise your own replacement heifers - Siefkas, R., author; Bentz, E., author; Blake, K., author; Platt, T., author; Valko, J., author; Hadrich, J., author; Department of Agricultural and Resource Economics, Colorado State University, publisher (Colorado State University. Libraries, 2017)
In the production cycle of a cow-calf enterprise, the producer will face the decision of replacing their older cows. The producer deciding to replace older cows with heifers has the following options: raise their own replacement heifers, buy open heifers and breed them, or buy bred heifers. The options vary in price, timing, and expense. The tool created is a cost-effective analysis between the three options: buying bred, buying open, or raising their own heifers.
PFC herd replacement comparisons (version 1) - worksheet
September 2017.
Zip file contains: worksheet.
Keywords: heifer replacement; budgets; Enterprise Budget